Lived experiences of children and adolescents with obsessive-compulsive disorder: interpretative phenomenological analysis - Lakshmi Sravanti; John Vijay Sagar Kommu; Satish Chandra Girimaji; Shekhar Seshadri (BMC, 2022)
Key message Delay in recognition of symptoms contributes to significant distress to the individual and family in cases where help is sought. There is a need to improve awareness so as to identify the problems early. This will improve help-seeking behaviour and aid in reducing peer victimization. Therapist-related barriers contribute to delays in making a diagnosis. Treatment is likely to positively impact other spheres of the child's life such as academics and interpersonal relationships and result in more long-term benefits. Bullying in school-context is a common occurrence.